Hypertrophy and neuron loss: structural changes in sheep SCG induced by unilateral sympathectomy - Fioretto, Emerson T.; Rahal, Sheila Canevese [UNESP]; Borges, Alexandre Secorun [UNESP]; Mayhew, Terry M.; Nyengaard, Jens R.; Marcondes, Julio S. [UNESP]; Balieiro, Julio C. de Carvalho; Teixeira, Carlos Roberto [UNESP]; Melo, Mariana P. de; Ladd, Fernando V. Lobo; Ladd, Aliny A. B. Lobo; Lima, Ana R. de; et al. (Pergamon-Elsevier B.V. Ltd, 2011)
Recently, superior cervical ganglionectomy has been performed to investigate a variety of scientific topics from regulation of intraocular pressure to suppression of lingual tumour growth. Despite these recent advances in our understanding of the functional mechanisms underlying superior cervical ganglion (SCG) growth and development after surgical ablation, there still exists a need for information concerning the quantitative nature of the relationships between the removed SCG and its remaining contralateral ganglion and between the remaining SCG and its modified innervation territory. To this end, using design-based stereological methods, we have investigated the structural changes induced by unilateral ganglionectomy in sheep at three distinct timepoints (2, 7 and 12 weeks) after surgery. The effects of time, and lateral (left-right) differences, were examined by two-way analyses of variance and paired t-tests. Following removal of the left SCG, the main findings were: (i) the remaining right SCG was bigger at shorter survival times, i.e. 74% at 2 weeks, 55% at 7 weeks and no increase by 12 weeks, (ii) by 7 weeks after surgery, the right SCG contained fewer neurons (no decrease at 2 weeks, 6% fewer by 7 weeks and 17% fewer by 12 weeks) and (iii) by 7 weeks, right SCG neurons were also larger and the magnitude of this increase grew substantially with time (no rise at 2 weeks, 77% by 7 weeks and 215% by 12 weeks). Interaction effects between time and ganglionectomy-induced changes were significant for SCG volume and mean perikaryal volume. These findings show that unilateral superior cervical ganglionectomy has profound effects on the contralateral ganglion. For future investigations, it would be interesting to examine the interaction between SCGs and their innervation targets after ganglionectomy. Is the ganglionectomy-induced imbalance between the sizes of innervation territories the milieu in which morphoquantitative changes, particularly changes in perikaryal volume and neuron number, occur? Mechanistically, how would those changes arise? Are there any grounds for believing in a ganglionectomy-triggered SCG cross-innervation and neuroplasticity? (C) 2011 ISDN. Published by Elsevier Ltd. All rights reserved.
Keywords: Superior cervical ganglionectomy; Stereology; SCG; Sheep